Dentine disorders and adhesive treatments: A systematic review. (June 2021) - Massé, Léa; Etienne, Olivier; Noirrit-Esclassan, Emmanuelle; Bailleul-Forestier, Isabelle; Garot, Elsa
Abstract: Objectives: A better understanding of the microstructure and mechanical properties of enamel and dentine may enable practitioners to apply the current adhesive dentistry protocols to clinical cases involving dentine disorders (dentinogenesis imperfecta or dentine dysplasia). Data/sources: Publications (up to June 2020) investigating the microstructure of dentine disorders were browsed in a systematic search using the PubMed/Medline, Embase and Cochrane Library electronic databases. Two authors independently selected the studies, extracted the data in accordance with the PRISMA statement, and assessed the risk of bias with the Critical Appraisal Checklist. A Mann-Whitney U test was computed to compare tissues damage related to the two dentine disorders of interest. Study selection: From an initial total of 642 studies, only 37 (n = 164 teeth) were included in the present analysis, among which 18 investigating enamel (n = 70 teeth), 15 the dentine-enamel junction (n = 62 teeth), and 35 dentine (n = 156 teeth). Dentine is damaged in cases of dentinogenesis imperfecta and osteogenesis imperfecta (p = 2.55E-21 and p = 3.99E-21, respectively). These studies highlight a reduction in mineral density, hardness, modulus of elasticity and abnormal microstructure in dentine disorders. The majority of studies report an altered dentine-enamel junction in dentinogenesis imperfecta and in osteogenesis imperfecta (p = 6.26E-09 and p = 0.001, respectively). Interestingly, enamel is also affected in cases of dentinogenesis imperfecta (p = 0.0013), unlike to osteogenesis imperfecta (p = 0.056). Conclusions: Taking into account all these observations, only a few clinical principles may be favoured in the case of adhesive cementation: (i) to preserve the residual enamel to enhance bonding, (ii) to sandblast the tooth surfaces to increase roughness, (iii) to choose a universal adhesive and reinforce enamel and dentine by means of infiltrant resins. As these recommendations are mostly based on in vitro studies, future in vivo studies should be conducted to confirm these hypotheses.